Spatial specificity of auxin responses coordinates wood formation - Brackmann, Klaus; Qi, Jiyan; Gebert, Michael; Jouannet, Virginie; Schlamp, Theresa; Wallner, Eva-Sophie; Lohmann, Jan U.; Greb, Thomas (Nature Communications, 2018)
Auxin activity controls plant stem cell function. Here the authors show that in the cambium, moderate auxin activity restricts cambial stem cell number via ARF5-dependent repression of the stem‐cell‐promoting factor WOX4, while ARF3 and ARF4 promote cambial activity outside of the WOX4‐expression domain.
Gesehen am 23.07.2019